MEDIA THAT NO LONGER MEDIATE: the blurred enunciation in contemporary journalistic practices - Gambetta Abella, Leticia; Huertas, Agustina (Brazilian journalism research, 2024)
ABSTRACT – This study analyzes the place of enunciation that is configured from the publication of an article by certain journalists from the Uruguayan newspaper El Observador, about a case of corruption in the national government. The particularity of this case lies mainly in the journalists who chose their X accounts instead of the written medium, to spread the information. The analysis of these publications within the framework of critical discourse analysis of social networks leads to the identification of spaces of enunciation that blur the limits of media enunciation and make contemporary communication unpredictable. RESUMO – Este trabalho analisa o lugar de enunciação que se configura a partir da publicação de uma notícia por parte de certos jornalistas do jornal uruguaio El Observador, sobre um caso de corrupção no governo nacional. A particularidade deste caso reside principalmente no fato de que os jornalistas escolheram suas contas no X em vez do meio escrito, para divulgar a informação. A análise dessas publicações sob o marco da análise crítica do discurso de redes sociais leva à identificação dos espaços de enunciação que desfocam os limites da enunciação midiática e tornam imprevisível a comunicação contemporânea. RESUMEN – Este trabajo analiza el lugar de enunciación que se configura a partir de la publicación de una noticia por parte de ciertos periodistas del diario uruguayo El Observador, sobre un caso de corrupción en el gobierno nacional. La particularidad de este caso radica principalmente en que los periodistas escogieron sus cuentas de X en lugar del medio escrito, para difundir la información. El análisis de dichas publicaciones bajo el marco del análisis crítico del discurso de redes sociales, conduce a identificar los espacios de enunciación que desdibujan los límites de la enunciación mediática y vuelven impredecible la comunicación contemporánea.